Disruptive Behaviour: Managing the Challenges and Issues - A Case Study - V. , Anuradha; R. , Pushkala (International Journal of Psychosocial Rehabilitation, 2020)
Disruptive behavior has become one of the most important concerns of this era. Though the teachers are prepared to use instructional strategies and to make sure that all students excel academically, many perspective teachers are not adequately prepared to deal with disruptive student behavior. So in reality, managing the challenges and issues of disruptive behavior is still an illusion. It may have some of their own specific causes, but there are also some general conditions that make disruptive behavior more likely to occur. This may include poor parenting and poor teaching. The first thing that a teacher has to think is if a student is disrupting the class, then it is because of the teaching method followed in the class. Even the most disruptive students will sit for hours together on computer games or engage themselves in other hobbies that they really enjoy, so it may be due to the lesson, and the method that is taught may not be interesting. This study shares how the disruptive behavior of the two section students from first-year B.Tech and first-year B.A. English was dealt with carefully and effectively by making them involved in sharing their personal narration. Once they started sharing their personal experiences, they also shared their emotional experiences, which created a good rapport and bond between the teachers. The bond completely changed the behavior of the students on the whole, and by the end of the year they were so obedient, and the last working day turned emotional.